Experimental evaluation of an integrated demand response program using electric heat boosters to provide multi-system services. (15th February 2020) - Cai, Hanmin; Thingvad, Andreas; You, Shi; Marinelli, Mattia
Abstract: The share of renewable energy resources (RES) production has been increasing in both the electricity system and the district heating (DH) system in Denmark. This challenges system operators' traditional operating practices in which different energy systems are separately managed and end-users play a passive role in the system operation. Integrated energy system operation considering multiple energy carriers is increasingly perceived as a key approach to accommodate the RES in a globally optimal way. Although existing literature has analysed (DR)'s potential for improving system operation, it has been largely confined to a single energy system. To fill this gap, the current study focuses on (IDR)'s potential for improving the operation of integrated electricity and DH system. This paper presents one of the first experimental demonstrations of an IDR program by deploying electric heat boosters (EHBs) to provide multi-system services. The multi-scale demonstration of the IDR program was structured into three hierarchical levels: (i) augmented commercial DH substations; (ii) distributed situation-aware control systems; and (iii) an aggregation controller. The results show that EHBs in 5 single-family buildings simultaneously delivered frequency-controlled normal operation reserve (FCR-N) with a symmetric capacity of 7.5 kW to the electricity system with an activation time of 4 s and a peak shaving service to the DH system. The temperature distribution over the test period revealed that end-user comfort was maintained. In conclusion, EHBs in an IDR program can simultaneously support both the electricity system and the DH system, which provides system operators' a tool for integrated system operation; the multi-system service design enhances the economic outlook of active demands in an IDR program. Highlights: One of the first worldwide experimental demonstrations of integrated demand response. FCR-N service was delivered with an activation time of 4 s. Multiple services were delivered to electricity and district heating system. Experiments show end user comfort was maintained in all cases.